2003
DOI: 10.1521/jscp.22.6.716.22932
|View full text |Cite
|
Sign up to set email alerts
|

Stressors for Gay Men and Lesbians: Life Stress, Gay-Related Stress, Stigma Consciousness, and Depressive Symptoms

Abstract: Gay-related stress occurs when gay men and lesbians must deal with stressors that are unique to their sexual orientation. This research examined the relationship of gay-related stress and life events to depressive symptoms. Other potential predictors of depressive symptoms were also considered (internalized homophobia, stigma consciousness, and openness about sexual orientation). A sample of 204 (110 men, and 91 women, three sex-unspecified) gay/lesbian/bisexual individuals completed a packet of self-report me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
267
0
5

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 399 publications
(301 citation statements)
references
References 16 publications
29
267
0
5
Order By: Relevance
“…In a study of 204 lesbian, gay, bisexual and/or transgendered individuals (LGBT) researchers found that gay-related stress and life stress account for a significant proportion of variance in depressive symptomatology. Furthermore, gay-related stress accounted for unique variance in depressive symptomatology, which supports the hypothesis that minority stress is distinct from generalized life stress and occurs above and beyond levels of generalized life stress (Lewis, Derlega, Griffin, & Krowinski, 2003).…”
Section: Chapter 2 Literature Review Perceived Stress In Minority Popsupporting
confidence: 70%
See 1 more Smart Citation
“…In a study of 204 lesbian, gay, bisexual and/or transgendered individuals (LGBT) researchers found that gay-related stress and life stress account for a significant proportion of variance in depressive symptomatology. Furthermore, gay-related stress accounted for unique variance in depressive symptomatology, which supports the hypothesis that minority stress is distinct from generalized life stress and occurs above and beyond levels of generalized life stress (Lewis, Derlega, Griffin, & Krowinski, 2003).…”
Section: Chapter 2 Literature Review Perceived Stress In Minority Popsupporting
confidence: 70%
“…The minority stress model (Meyer, 1995; posits that stigmatization, discrimination and prejudice experienced by sexual minorities increase vulnerability to psychosocial stress, above and beyond stress related to daily hassles (Harrell, 2000;Meyer, 2003;Wei, Ku, Russell, Mallinckrodt, & Liao, 2008). This stress is nearly constant, and can result in the experience of chronic stress (Lewis, Derlega, Griffin, & Krowinski, 2003;Meyer, 2003). In a study of 204 lesbian, gay, bisexual and/or transgendered individuals (LGBT) researchers found that gay-related stress and life stress account for a significant proportion of variance in depressive symptomatology.…”
Section: Chapter 2 Literature Review Perceived Stress In Minority Popmentioning
confidence: 99%
“…This hypothesis is based on evidence that members of stigmatized groups differ in the extent to which they expect to be targets of negative stereotypes and discrimination (Mendoza-Denton et al, 2002;Pinel, 1999). Individuals who expect to be rejected Eccleston & Major appraisals of discrimination 149 based on a stigmatized social identity pay more attention to subliminally presented information that is threatening to their social identity, are more distrustful of outgroup members, are more anxious in intergroup settings, and are more depressed compared to those lower in expectations of prejudice (Kaiser, Vick, & Major, in press;Lewis, Derlega, Griffin, & Krowinski, 2003;Mendoza-Denton et al, 2002;Pinel, 1999). Consistent with a stress and coping perspective, we hypothesized that individuals who tend to attribute ambiguous events to discrimination are vulnerable to lower self-esteem, to the extent that they also tend to appraise discrimination in more harmful ways.…”
Section: Determinants Of Discrimination Appraisalsmentioning
confidence: 99%
“…Stigma consciousness, the extent to which targets of stereotypes are aware of them and expect to be stereotyped, has important influences on how people experience and behave in stereotype-relevant situations (Pinel, 1999). Higher levels of stigma consciousness with regard to one's sexual orientation are related to depressive symptoms and mental health well-being in general (Berghe, Dewaele, Cox, & Vincke, 2010;Lewis, Derlega, Griffin, & Krowinski, 2003). Moreover, people high in stigma consciousness have been shown to avoid stereotype-relevant situations in which there are opportunities to confirm the stereotype (Pinel, 1999), which may be particularly relevant for medical encounters.…”
mentioning
confidence: 99%